HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KECEPATAN REAKSI TERHADAP LARI 100 YARD PADA ATLET PPLP RIAU - Mentari Pratiwi; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem of there is a correlation between explosive power and reaction speed with runs 100 yard on athletics team PPLP Riau. The forms of this research are the correlation study, the population in this study from the athletics team PPLP Riau, and the sample in this study athlete athletics team PPLP Riau numbered 12 people. The first analysis in the calculation of the correlation between X1 and Y, where rtable at significant level α (0,05) = 0.602 mens rresult (0.657)> rtable (0,602), which means the hypothesis is accepted and there is a meaningful correlation between explosive power with runs 100 yard on the men’s athletics team PPLP Riau, a second analysis of reaction speed (X2) with 100yard (Y), where rtable at significant level α (0,05) = 0.602 means rresult (0.607)> rtable (0,473), which means the hypothesis is accepted and there is a correlation the between 100 yard ability in athlete athletics team PPLP Riau, the analysis of the three correlations explosive power (X1) and reaction speed (X2) with the 100yard (Y) was obtained, which rtable at significant level α (0,05) = 0.602 , means rresult (0.811)> rtable (0,602). Then it can be concluded that the correlation between (X1) and (X2) with Y or the correlation between the explosive power and reaction speed with 100 yard are significant. Therefore the athletics athlete run ability from men’s athletics team PPLP Riau in the forecast with their explosive power and reaction speed.Keywords: Explosive Power, Reaction Speed, 100 yard